Teaching Rational Thinking Skills in Indonesian Junior High School - Anjar Mukhoyaroh (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
In some cases, the ability to adopt a global perspective becomes dominant as the rate of development of the ages takes place for various activities to bring about positive impacts. In the study of the underlying philosophy of humanity which is a positive assessment of the things that resemble the basics of existence and diversity of each and community self that is meaningful to the existence of each knowledge or community. It can adjust the knowledge line as well as the skills to adapt, and the ability to adapt to the capabilities and skills of adequate knowledge in addition to the skills for designing knowledge for various things is the basis for making knowledge dominant in line with the rate of development of information and communication. Technology and enhancement of skills are the identities of learners in the development of skills to build skills in assessment philosophy expressed in various sectors that are expected to conform to the ability and skill to complete.